2019
DOI: 10.1071/mf18222
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of meiofaunal tardigrades in a small tropical estuary (~6°S; Brazil)

Abstract: Spatial variations and organism–sediment relationship are paramount subjects of soft-bottom ecology. However, these issues have been unexplored for most minor meiofaunal taxa such as tardigrades. In the present study, we explore this subject on a small tropical (~6°S) estuary. Total meiofaunal abundance ranged from 4 to 1036 individuals per 10cm2, averaging (mean±s.d.) 324.8±245.9 individuals per 10cm2. Nematodes dominated in both seasons, representing >70% of total abundance. Tardigrades were the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Tardigrade responses to small-scale habitat heterogeneity (patchiness) could explain the high variability among pseudoreplicates as shown to be the predominant source of variance for all six examined indexes (Table 2). Leetham et al (1982) and Hohberg (2006) also found a high intrasite variance in the number of tardigrades in soil habitats, and a similar level of patchiness has been shown for other substrates as well (Meyer, 2006;Sohlenius et al, 2004;Tilbert et al, 2019). In our experimental setup, soil moisture was not correlated with air temperature and was instead correlated with air relative humidity (Burt et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Tardigrade responses to small-scale habitat heterogeneity (patchiness) could explain the high variability among pseudoreplicates as shown to be the predominant source of variance for all six examined indexes (Table 2). Leetham et al (1982) and Hohberg (2006) also found a high intrasite variance in the number of tardigrades in soil habitats, and a similar level of patchiness has been shown for other substrates as well (Meyer, 2006;Sohlenius et al, 2004;Tilbert et al, 2019). In our experimental setup, soil moisture was not correlated with air temperature and was instead correlated with air relative humidity (Burt et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Leetham et al. (1982) and Hohberg (2006) also found a high intrasite variance in the number of tardigrades in soil habitats, and a similar level of patchiness has been shown for other substrates as well (Meyer, 2006; Sohlenius et al., 2004; Tilbert et al., 2019). In our experimental setup, soil moisture was not correlated with air temperature and was instead correlated with air relative humidity (Burt et al., 2014).…”
Section: Discussionmentioning
confidence: 67%
“…These are factors which all reduce the abundance of interstitial fauna (Monterey Bay at National Marine Sanctuary, 2019). Granulometry was suggested as the most important environmental factor for structuring meiofauna in tropical estuaries (Tilbert, de Castro, Tavares, & Júnior, 2019). Our results also showed that sediment particle size was an important environmental variable affecting the composition and distribution of nematode assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…The taphonomic cluster followed a geographic pattern, since Lucena and Miramar were close to each other in the north and reflects their deposition and abrasion dynamics. For the taxonomic cluster the characteristic of the type of the sediment of each beach was preponderant; while medium and coarse gains predominated in most sampled beaches, at Miramar fine and very fine sand predominated (~80%), what usually is associated to higher organic content (Moore 1958, Ferreira 1977, 1978, Tilbert et al 2019. In addition, Miramar seems to be becoming a lagoon, with very low hydrodynamic energy and high salinity.…”
Section: Foraminifera -Taphonomic Structurementioning
confidence: 99%